Anti-diabetic and pancreatoprotective effects of stingless bee honey in streptozotocin-nicotinamide-induced diabetic rats. - Muhammad Shakir Abdul Aziz (2017)
Stingless bee honey (SLBH) is produced by a stingless bee species namely Geniotrigona thoracica (G. thoracica). Honey has been claimed to have anti- diabetic effects. However, there has been no scientific proof to validate this claim for SLBH. In addition, the mechanisms underlying the anti-diabetic effect (if any) of this honey has not been reported previously. In the current study, the effect of SLBH on biochemical and biological parameters such as fasting blood glucose (FBG), lipid profiles, insulin, body weight, food and water intake were investigated. Effects of SLBH consumption on pancreas morphology, histopathology, oxidative stress, inflammation and apoptosis were also investigated. The findings indicated that 28- days oral administration of SLBH at 1 and 2 g/kg body weight have prevented the increase in FBG, total cholesterols, triglyceride and LDL cholesterol and the decrease in HDL-cholesterol and insulin levels. Administration of SLBH also has ameliorated histopathological changes in the pancreatic islets and preserved the morphology of the pancreas and pancreatic islets to a near normal condition. Meanwhile, increased oxidative stress, inflammation and apoptosis in diabetic rats’ pancreas were ameliorated following 28-days administration of SLBH. SLBH was found to display a dose-dependent effectiveness. Effects of 2 g/kg body weight SLBH was found to be almost identical to the effects exerted by glibenclamide (positive control). In conclusion, SLBH could be used as anti-diabetic agent as it has pancreatoprotective effects.